Determination of proximate composition, selected essential and heavy metals in sesame seeds (Sesamum indicum L.) from the Ethiopian markets and assessment of the associated health risks. (2022) - Beshaw, Tamene; Demssie, Kindnew; Tefera, Molla; Guadie, Atnafu
Abstract: In this study, the proximate composition, levels of essential and heavy metals; and health risk assessment were evaluated in sesame seed ( Sesamum indicum L.) samples purchased randomly from local markets of three study sites in Ethiopia. A 0.15 g of dried and homogenized samples were digested using 6 mL of HNO3 (69–72%) and 3 mL of HClO4 (70%) at 120 °C for 3 h. The levels of proximate composition and essential metals in the sesame samples were determined by the Association of Official Agricultural Chemists (AOAC) and Flame Atomic Absorption Spectrometer (FAAS), respectively. The moisture content, crude fiber, ash content, fat, crude proteins and carbohydrate of sesame samples ranged between 3.15% and 5.52%, 4.21–4.40%, 3.10–4.75%, 55.75–56.9%, 22.65–23.39% and 8.34–8.80%, respectively. The accuracy of the procedure was validated by percent recovery of samples for all metals varied from 85.60% to 102.00%. The mean levels of the metals (mg/kg) were found in the range of 37.20–70.10 (Na), 315.1–338.00 (K), 209.00–216.50 (Mg), 328.00–341.30 (Ca), 12.60–12.90 (Fe), 4.90–5.00 (Cu) and 8.30–8.70 (Zn) mg/kg. The THQ values of heavy metals were found < 1, indicating that the consumption of sesame may not cause health risks to local consumers. The values of HI ranged from 1.5 × 10 −3 to 1.8 × 10 −3 in the study areas and may not have a possible adverse health effect on the adult population from the consumption of sesame seeds. Graphical Abstract: ga1 Highlights: Proximate, metals composition and associated health risk assessment of trace metals. Association of Official Analytical Chemists method was employed proximate analysis. Flame atomic absorption spectroscopy technique was applied for metal analysis. The method was validated with low LODs good linearity, and high recoveries. THQ and HI of Zn, Cu, and Fe did not contribute to non-cancer effects on human health.